CORNEAL TRANSPLANTATION: UPDATES ON TRANSPLANTATION TECHNIQUES AND TREATMENTS FOR REJECTION - Pedro do Valle Varela, João; Gava, Lara; Salvadora Cunha Brito, Shaira; Vieira Lobo Jardim Pimentel, Renata; Vieira Praxedes, Danielle; Borges Meirelles, Paula; Pedro Forechi Rodrigues, João; Oliveira Gil de Almeida, Yasmin; Cruz Orsi, Verena; Luiz Teixeira Fully, Fabio (Health and Society, 2024)
Corneal transplantation is an ophthalmic surgery that aims to restore vision in patients with corneal diseases. Advances in transplantation techniques and in the treatment of rejection have improved the results of this procedure, making it more effective and safer. This paper seeks to analyze the latest developments in transplantation techniques and treatments for rejection in corneal transplantation, highlighting not only scientific advances, but also the emotional and social aspects involved in this procedure, providing a comprehensive overview of the latest innovations in the field of corneal transplantation, highlighting improvements in surgical techniques and post-operative treatments, which are helping to transform the lives of thousands of patients around the world. This is a bibliographical review, using qualitative premises, with the PubMed, Scopus, Web of Science and Scielo databases. The health descriptors “corneal transplantation”, “corneal graft rejection” and “penetrating keratoplasty” were used to better refine the research. Corneal transplantation is indicated for various conditions, such as keratoconus, corneal dystrophies, corneal opacities, among others. The most common transplant techniques include complete (penetrating) corneal transplantation, anterior lamellar transplantation and endothelial transplantation (DSAEK/ DMEK). In recent years, there have been significant advances in lamellar transplantation techniques, which allow specific layers of the cornea to be replaced while preserving the healthy layers. This has resulted in better success rates and faster visual recovery compared to penetrating transplantation. Treatment of corneal graft rejection includes the use of topical and systemic corticosteroids, immunosuppressants and anti-inflammatory agents. New approaches, such as biological and immunomodulatory therapies, are also being investigated to improve results in cases of refractory graft rejection. In conclusion, corneal transplantation remains an important option for restoring vision in patients with corneal diseases. Updates in transplantation techniques and advances in the treatment of rejection have improved the results of this procedure, providing patients with a better quality of life and faster and more effective visual recovery.